Analysis of Public Service Quality from Tangible and Reliability Dimensions (Case Study at the Population and Civil Registration Office of Empat Lawang Regency): Analisis Kualitas Pelayanan Publik dari Dimensi Tangible dan Reliability (Studi Kasus di Dinas Kependudukan dan Catatan Sipil Kabupaten Empat Lawang) - Pandriansyah, Pandriansyah; Sigiro, Benny (Gayaku Publisher, 2024)
Optimal public service is an important aspect in increasing public trust and satisfaction. However, various obstacles are still faced by government agencies in providing adequate services. This study aims to analyze the quality of public services at the Population and Civil Registration Service (Disdukcapil) of Empat Lawang Regency through two main dimensions, namely tangible and reliability. This study uses a qualitative descriptive method with data collection techniques in the form of observation, interviews, and documentation studies. The results of the study indicate that the implementation of the tangible dimension at Disdukcapil is not optimal, as seen from inadequate physical facilities, such as uncomfortable waiting rooms and equipment that often experiences problems. In the reliability dimension, unreliable services were found, especially in terms of consistency and timeliness, due to limited human resources and less supportive technological equipment. The main inhibiting factors include budget constraints, lack of employee training, and limited technological infrastructure. The implications of this study indicate the need for improvements in terms of budget, employee training, and improvements in technological infrastructure to meet public expectations for better and more reliable services.